Ethnolinguistics and Cultural Concepts : Truth, Love, Hate and War. - Underhill, James W. (Cambridge University Press, 2012)
An original approach to ethnolinguistics, discussing how abstract concepts such as love and hate are expressed across cultures and ethnicities.